Municipal and Treasury Bond Market Segments Development at Bucharest Stock Exchange - Cornelia POP; Maria- Andrada GEORGESCU (Transylvanian Review of Administrative Sciences, 2012)
The current paper reviews the developments that took place, starting with November 2001, inside the Romanian Municipal and Treasury bond market segments at the Bucharest Stock Exchange. The development of a debt market has as a main objective to encourage the central, regional and local governments to consider bond finance as an important way for regional and local project investments; it could enhance the quality and the efficiency of financed projects and encourage long term financial planning. The relatively modest profile of the Romanian public bond sector at Bucharest Stock Exchange can be explained by the late introduction of the T-bonds (7 years after the bond sector was launched). Lacking the benchmark the T-bonds could offer, it was only natural for investors to avoid the (Municipal) bond sector. The development of the domestic public bond sector is expected to continue in the years to come, mainly if through bond financing the central/regional and local authorities will support investment projects that will trigger and/or generate economic development.